Protein profile in breast cancer patients undergoing doxorubicin treatment : an iTRAQ-coupled LC-MS/MS approach - Cheah, Chee Liang. (2009)
Chemotherapy is a common treatment for breast cancer and Doxorubicin is a common chemotherapeutic drug used for this purpose. However drug resistance is a great limitation to the effectiveness of chemotherapy treatment. It has been discovered that patients with single nucleotide polymorphism (SNP) in Murine Double Minute 2 (MDM-2) gene promoter have higher resistance to chemotherapeutic treatment with Doxorubicin.